Pandangan Dunia Pengarang Novel Bandung Menjelang Pagi Kajian Strukturalisme Genetik Lucien Goldmann: Penelitian - Herson Kadir; Zilfa Achmad Bagtayan; Ratna Hanapi; Cindriawati Pomolango; Zaqia Debila P. Deu; Oktafiyani Mooduto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study analyzes the author's worldview in Brian Khrisna's novel Bandung Nearing Morning using Lucien Goldmann's genetic structuralism approach. This study aims to reveal the relationship between the novel's narrative structure and the social structure of urban society as represented through themes, conflicts, characters, and settings. The research method used is descriptive qualitative with textual analysis of intrinsic elements containing expressions of collective ideas and values. The research findings show that this novel presents the dynamics of urban life characterized by identity crises, the pressures of modernity, the disintegration of social relations, and the existential struggles of its characters. The city of Bandung functions as a social space that mediates the characters' psychological conflicts and reflects the conditions of contemporary society. The author's worldview is reflected through criticism of the fast-paced urban lifestyle as well as messages about the importance of self-reflection, emotional health, and the restoration of human relations. This novel, therefore, functions as a social representation that integrates personal experiences and historical contexts in its narrative structure.